Sistem Informasi Laboratorium Karantina Hewan Dibalai Karantina Hewan Ikan Dan Tumbuhan Bengkulu Menggunakan PHP Dan MySQL - Tri Ramadani; Asnawati Asnawati; Achmad Fikri Sallaby (Jurnal Media Infotama, 2025)
Animal, Fish, and Plant Quarantine Center of Bengkulu plays an important role in maintaining the safety and health of animals, fish, and plants entering or leaving Indonesia. One of the main activities in supporting this task is laboratory testing. However, the process of managing laboratory data, which is still done manually, often causes various problems, such as delays in recording, data duplication, and difficulties in searching and reporting data. To overcome this, a computerized Animal Quarantine Laboratory Information System was developed. This system was developed using PHP programming language and MySQL database, and was designed to manage test sample data, test results, laboratory reports, and other digital archives in an efficient and structured manner. The system development method used was waterfall, starting from needs analysis to system implementation. The results of this system development show that the laboratory data management process has become faster, more accurate, and more accessible to relevant parties. Thus, this information system is expected to improve service quality and operational efficiency at the Bengkulu Animal, Fish, and Plant Quarantine Center laboratory.